Literature Review: Evolusi Strategi Pemasaran Digital dalam Era Teknologi Informasi - Anita Rahmawati; Sri Isti Untari; Kristin Lukitaningrum; Maria Nino Istia; M. Jamal Al Bakri (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
The age of information technology has brought about major transformations in various aspects of business, particularly in the field of marketing. This article aims to conduct a comprehensive literature review on the evolution of digital marketing strategies, describing the paradigm shifts and techniques used by companies in adapting to technological advancements. The literature review approach allows this research to analyze academic studies from various reputable national and international journals to formulate an evolutive understanding of digital marketing, encompassing the shift from traditional strategies towards interactive and data-driven approaches. The findings of the article reveal that digital marketing not only increases the effectiveness of marketing communications, but also raises new challenges that must be addressed by practitioners and academics. This research is expected to contribute to the development of more adaptive and effective marketing strategies in the future, as well as provide an overview of how recent trends in digital marketing are shaping the competitive business landscape. With technological advancements, from social media to big data to artificial intelligence, the evolution of digital marketing continues at a rapid pace, requiring an in-depth understanding of relevant principles and practices. The study also highlights the importance of developing a company's digital capabilities to ensure the success of its marketing strategy in this era of digitization.